PERAN PENYULUHAN DALAM PEMBERDAYAAN PETANI KELAPA POLA SWADAYA DI DESA BENTE KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR - Yulida, Roza; ', Pariaman; ', Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study are: (1).To determine the implementation of agricultural extension in the village of Bente; (2).To determine the role of education and the empowerment of farmers in the coconut farm self pattern; (3) To analyze the relationship counseling role towards the empowerment of farmers. This research was conducted in the village of Bente District of Mandah Indragiri Hilr. The sampling method used is purposive sampling method with consideration that the location of its extension activities and the active oil production areas. 30 self-help coconut farmers were taken as respondents. Analyzing the validity and reliability of measuring instruments. Analysis of the data to answer the first goal is to use descriptive qualitative, the second destination using a Likert scale. On the third goal using Spearman rank correlation analysis. The results showed: (1).In the implementation of the extension such as the elements of counseling in the village of Bente quite done well. (2). The extension .peran overall quite a role in non-farming activities coconut pattern, consisting of variable education, information dissemination, and consultation is instrumental category and facilitation, supervision, and monitoring and evaluation are in a category quite a role. Empowerment of farmers as a whole has cukub powerless in empowering self-help coconut farmers pattern, consisting of variable human resources, productive economy and institutions are in a category quite helpless. (3). Relationship counseling role towards the empowermentof self-help coconut farmers patterns are at the level of the relationship is strong enough, powerful and significant. Â  Keywords: Role of extension, Empowerment, Coconut Farmersself-Patterns.